The Result Development of Teaching Activities of Thai Literature by Using the DACIR Instructional Process for Student Bachelor of Education Program in Thai Language - Chotchuang, Chanitta (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: The development of teaching and learning will encourage learners to achieve the objectives of the Thai Literature Development course through the organization of teaching and learning activities that focus on students asking important questions and formulating assumptions in the study. This correlates with the DACIR teaching and learning process, which aims to develop learners’ ability to think analytically, and inferiorly and interact with a variety of sources of information. Thus, the purpose was to study 1) The development of teaching activities of Thai literature by using the DACIR instructional process, 2) the Comparison of achievement for the development of Thai literature, and 3) the Satisfaction of the learner to teaching activities of the development of Thai literature. Methodology: The sample group was 60 people of 3rd-year students in the Thai program, semester 1/2022 at Thepsatri Rajabhat University by simple random sampling. The research tools include teaching activities of Thai literature by using the DACIR instructional process, measuring achievement, and satisfaction questionnaire. Data were analyzed by using context validity, mean, standard deviation, and t-test. Results: The results found that 1) teaching activities of the development of Thai literature by using the DACIR instructional process were context-valid at the highest level. 2) Achievement in the development of Thai literature after learning was higher than before learning with statistical significance at the .05 level. 3) The learners were satisfied with the teaching activities of the development of Thai literature at the highest level. Conclusion: It was found that learning activities in the Thai literature course using the DACIR method have the highest content validity and exhibit high learning effectiveness. Overall, learners expressed the highest satisfaction with these activities.